A CMOS-MEMS clamped–clamped beam displacement amplifier for resonant switch applications. (19th March 2018) - Liu, Jia-Ren; Lu, Shih-Chuan; Tsai, Chun-Pu; Li, Wei-Chang
Abstract: This paper presents a micromechanical clamped–clamped beam (CC-beam) displacement amplifier based on a CMOS-MEMS fabrication process platform. In particular, a 2.0 MHz resonant displacement amplifier composed of two identical CC-beams coupled by a mechanical beam at locations where the two beams have mismatched velocities exhibits a larger displacement, up to 9.96×, on one beam than that of the other. The displacement amplification prevents unwanted input impacting—the structure switches only to the output but not the input—required by resonant switch-based mechanical circuits (Kim et al 2009 22nd IEEE Int. Conf. on Micro Electro Mechanical Systems ; Lin et al 2009 15th Int. Conf. on Solid-State Sensors, Actuators, & Microsystems (TRANSDUCERS'09) ; Li et al 2013 17th Int. Conf. on Solid-State Sensors, Actuators, & Microsystems (TRANSDUCERS'13) ). Compared to a single CC-beam displacement amplifier, theory predicts that the displacement amplifying CC-beam array yields a larger overall output displacement for displacement gain beyond 1.13 thanks to the preserved input driving force. A complete analytical model predicts the resultant stiffness and displacement gain of the coupled CC-beam displacement amplifier that match well with finite element analysis (FEA) prediction and measured results.